Punishment of Children as Perpetrators of Maltreatment Based on Restorative Justice - Afifah Suwandi , Chika; Fitriciada Azhari , Aidul (Dinasti Research, 2024)
The purpose of this study is to examine and analyze the application of criminal sanctions against children as perpetrators of restorative justice-based persecution in Semarang District Court Decision Number 5/Pid.Sus/Anak/2018/PN Smg. The method of approach in this writing is normative juridical. The specification of this research uses analytical descriptive. The data source uses secondary data. Data collection techniques using document studies. To analyze the data, researchers used qualitative analysis methods. The judge in deciding the case of maltreatment committed by a child against a child resulting in serious injury with a restorative justice approach in the Semarang District Court Decision Number 5/Pid.Sus/Anak/ 2018/PN Smg which states that the Defendant ARNES POLINUS SILALAHI alias ARPOL BIN J. SILALAHI is legally and convincingly proven guilty of committing the crime of